Effect of Altitude Level on Surgical Outcomes of Laparoscopic Sleeve Gastrectomy for Patients With Morbid Obesity: A Multicentre Prospective Study. Issue 2 (15th April 2022) - El Nakeeb, Ayman; El Sorogy, Mohamed; Hamed, Hosam; Elrefai, Mohamed; Attia, Mohamed; Emile, Sameh Hany; Abdallah, Emad; Khafagy, Wael; Kayed, Taha; Sewefy, Alaa M.; AlMalki, Ahmad; Alqahtani, Ali N.; et al.
Abstract : Background: This study aimed to evaluate the impact of altitude level on surgical outcomes of laparoscopic sleeve gastrectomy (LSG) for patients with morbid obesity. Methods: At the normal altitude level, 808 patients underwent LSG, and 467 patients underwent LSG in high-altitude regions. The primary outcome was evaluated based on the postoperative morbidity rate. Secondary outcomes were evaluated based on operating time, mortality, hospital stay, percentage of total weight loss (TWL), and comorbidities improvement. Results: No significant differences were noted in-hospital stay, time to start oral intake, gastric leakage, overall complications, and hospital mortality between the 2 groups. Deep vein thrombosis, pulmonary embolism, and mesenteric vascular occlusion were significantly higher in high altitude [11 (1.3%) vs. 14 (3%), P =0.04; 8 (0.7%) vs. 11 (2.4%), P =0.01; 4 (0.5%) vs. 8 (1.7%), P =0.03, respectively]. Patients with normal altitude recorded a better %TWL than those at high altitude after 12 months (41±9 vs. 39±9.6, P =0.002) and after 24 months (41±8 vs. 40±9, P =0.009). In both groups, a significant improvement was noted in comorbidity after LSG. Conclusion: The %TWL significantly achieved with LSG in normal and high altitudes. After 12 and 24 months, the %TWL is significantly higher with LSG at normal altitudes. High altitude is associated with a high incidence of deep vein thrombosis, pulmonary embolism, and superior mesenteric vascular occlusion with LSG.